Effect of Plant Geometry and Nutrient Inputs from Organic and Inorganic Sources on the Growth and Yield Attributes of Rice (Oryza sativa L.) in Eastern U.P. - Saurabh Bharti; Anil Kumar Singh; Vishuddha Nand; Aman Bharti; Rudra Pratap Singh; Brijesh Kumar; Balveer Gautam; Dr. Rudra Pratap Singh (The Bioscan, 2025)
Rice (Oryza sativa L.) is the most important staple food of the Indian population. The present study was conducted at Agronomy Research Farm, Acharya Narendra Deva University of Agriculture and Technology, Kumar Ganj, Ayodhya, Uttar Pradesh, on silty loam soil during 2023–24 and 2024–25 to study the productivity of rice.